Staged Treatment of Chest Wall Radiation-Induced Ulcer With Negative Pressure Wound Therapy and Latissimus Dorsi Myocutaneous Flap Transplantation. Issue 5 (July 2019) - Li, Xiuqi; Zhang, Fan; Liu, Xujin; Cao, Zilong; Liu, Pei; Xia, Lin; Du, Min
Abstract : Abstract: Chest wall ulcer induced by postmastectomy radiation therapy (PRMT) remains challenging for plastic surgeons because of the reduced blood supply, fibrosis, and impaired cellular potential in the irradiated area. In this study, chest wall ulcer was treated with negative pressure wound therapy (NPWT) and the latissimus dorsi myocutaneous (LDM) flap reconstruction in 2 stages. A retrospective study was performed on consecutive patients with chronic radiation-induced ulcers in chest wall from June 2012 to June 2017. Surgical debridement and NPWT were performed in the first stage and the chest wall reconstructed by the LDM flap transplantation after extensive debridement in the second stage. There were 10 female patients with chest wall ulcers with a mean age of 60.3 years. The average duration of the ulcers was 21.2 months and the ulcers varied from 1 × 2 to 5 × 7 cm 2 . Histological examination denied any recurrent breast cancer or radiation-related malignancy. Negative pressure wound therapy was applied with 100 to 125 mm Hg negative pressure during a period of 5 to 7 days in the first stage. The LDM flap varied from 11 × 15 to 15 × 20 cm 2 . The mean follow-up was 25.9 months. All the flaps survived well with satisfactory appearance and there was no donor-site morbidity or ulcer recurrence during the follow-up period. The staged treatment of the chest wall radiation ulcer incorporated the benefits of NPWT and LDM flap. It is beneficial in increasing the blood and nutrient supply to the irradiated tissue, enhancing the debridement and promoting tissue healing, thus improving the flap survival and decreasing the ulcer recurrence.